Feasibility, impact, and priority of key strategies to enhance diverse and inclusive training programs in clinical and translational research: A mixed methods study. Issue 1 (25th August 2023) - Campbell, Jennifer A.; Walker, Rebekah J.; Dawson, Aprill Z.; Ozieh, Mukoso N.; Schmidt, Susanne; Shay, L. Aubree; Williams, Joni S.; Phillips, Shane A.; Egede, Leonard E.
Abstract: Background: Enhancing diversity in the scientific workforce is a long-standing issue. This study uses mixed methods to understand the feasibility, impact, and priority of six key strategies to promote diverse and inclusive training and contextualize the six key strategies across Clinical and Translational Science Awards (CTSAs) Program Institutions. Methods: Four breakout sessions were held at the NCATS 2020 CTSA Program annual meeting focused on diversity, equity, and inclusion (DEI) efforts. This paper focuses on the breakout session for Enhancing DEI in Translational Science Training Programs. Data were analyzed using a mixed methods convergent approach. The quantitative strand includes the online polling results. The qualitative strand includes the breakout session and the chat box in response to the training presentation. Results: Across feasibility, impact, and priority questions, prioritizing representation ranked number 1. Building partnerships ranked number 2 in feasibility and priority, while making it personal ranked number 2 for impact. Across each strategy, rankings supported the qualitative data findings in feasibility through shared experiences, impact in the ability to increase DEI, and priority rankings in comparison to the other strategies. No divergence was found across quantitative and qualitative data findings. Conclusion: Findings provide robust support for prioritizing representation as a number one strategy to focus on in training programs. Specifically, this strategy can be operationalized through integration of community representation, diversity advocates, and adopting a holistic approach to recruiting a diverse cadre of scholars into translational science training programs at the national level across CTSAs.